Systematic Literature Review: Implementation of Talent Management for Crewing in Shipping Companies to Organizational Sustainability - Wenny Desty Febrian; Indra Sani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to provide an explanation of scientific articles the results that have been by providing a qualitative graphical picture. An organized literature review is a component of the research methodology used in this scientific article. During the literature review, a number of relevant scientific articles are selected, excavated, and reviewed. The size of the study was determined by scores using the PICO framework (population/problem, intervention, comparison). The three scientific articles that support this article provide an illustration that the existing implementation of the findings of the above article is true even though only a few articles provide a finding that is directly related to the relationship of this article result. This article provides a treasure and additional reference for other researchers and for future development can be done.